Kesiapan Prasarana Mitigasi Bencana Pada Kawasan Rawan Bencana Erupsi Gunung Berapi Kabupaten Magelang - Ivan Yusuf; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2018)
Magelang regency has high volcanic eruption risk level from high to low. The 2010 eruption disaster was the most explosive among the others in the past decade. The high level of hazard with unpreparedness from community and the government in dealing with disasters in 2010 made poor evacuation. Based on these problems the assessment preparedness level of disaster infrastructure is important. Because it can reduce the impact of damage and disadvantages obtained by the community. The research question is